Pendampingan Pemasaran Digital Branding Kampung Malon - Septa Intiar; Krisnawati Setyaningrum Nugraheni; Mukhamad Kholil Aswan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This Community Service Program aims to provide digital marketing and branding assistance to Kampung Malon, a local community with tourism potential and superior products. Through this assistance, it is hoped that the local community can utilize digital technology to enhance the promotion and visibility of Kampung Malon. The mentoring method involves direct training and guidance to the residents of Kampung Malon regarding the concepts of digital marketing and effective branding techniques. Practical steps such as creating digital content, managing social media, and implementing online marketing strategies will be taught and applied together with the local community. In addition, this program will also assist in building the brand identity of Kampung Malon, focusing on local values, product uniqueness, and tourism attractions. Through the active involvement of residents, it is expected that the positive image of Kampung Malon can be strengthened, inviting tourist interest and supporting local economic growth. The results of this assistance will be evaluated periodically to measure its impact on increasing tourist visits, local product sales, and community participation in digital marketing activities. The conclusion of this program will provide insights into the effectiveness of digital marketing and branding strategies in the context of local communities like Kampung Malon. Thus, it is hoped that this program can become a model that can be adopted by similar communities in various regions to enhance their economic and tourism potential through the utilization of digital technology